Efficacy and safety of fruquintinib in the treatment of colorectal cancer: a systematic review and meta-analysis of studies in China - Feng, Yuan; Shu, Yu (Frontiers in Pharmacology, 2025)
ObjectivesTo evaluate fruquintinib’s efficacy and safety in the treatment of colorectal cancer.MethodsStudies assessing fruquintinib for colorectal cancer were included. Outcomes were overall survival (OS) and progression-free survival (PFS), and adverse reactions. A random-effects model was employed, and sensitivity analysis assessed the stability of the results and potential heterogeneity. Review Manager 5.4 and STATA 15.0 were used for analysis.ResultsEleven studies with 2,367 patients were included. Fruquintinib significantly improved OS (HR: 0.69; 95% CI: 0.58, 0.81; P < 0.00001) and PFS (HR: 0.44; 95% CI: 0.30, 0.64; P < 0.0001). No significant increase in adverse events, serious adverse events, fatigue, or hypertension. However, sensitivity analysis suggested that the risk of hypertension might be unstable, requiring further validation.ConclusionFruquintinib improves OS and PFS in colorectal cancer patients without elevating the risk of overall or serious adverse events; however, its potential impact on hypertension risk requires further investigation. Due to limitations such as small sample size, missing data, and regional bias, larger, multicenter, double-blind RCTs are needed to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD420251002004.